2018
DOI: 10.1111/1467-9477.12120
|View full text |Cite
|
Sign up to set email alerts
|

Who's Welcome and Who's Not? Opposition towards Immigration in the Nordic Countries, 2002–2014

Abstract: This article demonstrates the analytical advantages of studying not only the degree to which people oppose immigration in a country, but also the character of their opposition. Using Latent Class Analysis and data from the European Social Survey, Nordic patterns and trends are examined with the aim of identifying different kinds of immigration attitudes and how they develop in different national contexts. The Nordic countries are interesting to compare as, while they are similar in many respects, they also div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 87 publications
(101 reference statements)
1
2
0
Order By: Relevance
“…However, there is a clear difference in the strength of the two variables, as attitudes towards culturally dissimilar immigrants have a more than four times stronger effect than those towards culturally similar immigrants. This is in line with previous studies that indicate that Finns take differential positions on different immigrant groups (Bohman, 2018). The Russian population in Finland is often perceived as a realistic threat (Nshom and Croucher, 2014), which may explain why attitudes towards culturally similar groups have an effect in Finland.…”
Section: Resultssupporting
confidence: 93%
“…However, there is a clear difference in the strength of the two variables, as attitudes towards culturally dissimilar immigrants have a more than four times stronger effect than those towards culturally similar immigrants. This is in line with previous studies that indicate that Finns take differential positions on different immigrant groups (Bohman, 2018). The Russian population in Finland is often perceived as a realistic threat (Nshom and Croucher, 2014), which may explain why attitudes towards culturally similar groups have an effect in Finland.…”
Section: Resultssupporting
confidence: 93%
“…How does the ethnic majority in Europe react to these significant developments and to Muslim immigration? In a cross-national study, Abdelaaty and Steele (2022) report that majority members’ opposition to Muslim immigration is common, but they also found that mass-level reactions toward immigration and immigrants are not uniform (see also Bohman 2018). How should this non-uniform pattern at the mass level be conceptualized?…”
Section: Pure Liberals and The Power Of Prejudicementioning
confidence: 99%
“…The inflow of Muslims from the Middle East to European nations is provoking varying popular reactions among majority members (Gusciute, Mühlau and Layte 2021). In Western democracies, some segments of the majority group oppose Muslim immigration, while others support it (Bohman 2018). But do the supporters of Muslim immigration accept Muslims without hesitation?…”
Section: Introductionmentioning
confidence: 99%